Thermal and functional group characterization of cellulose from sugarcane bagasse - Plermjai, Kittiya; Termkoa, Krongtip; Meechowas, Ekarat; Pecharapa, Wisanu (Bulletin of Applied Sciences, 2022)
This research has focused on the characterization of cellulose from sugarcane bagasse by thermal and functional group analysis. Cellulose was extracted from sugarcane bagasse using chemical treatment with sulfuric acid, sodium hydroxide and hydrogen peroxide. Fourier transform infrared spectrophotometer (FTIR) analysis showing the evidence of hemicellulose and lignin removed from sugarcane bagasse after chemical treatment investigated chemical functional groups of the prepared cellulose.Crystalline structures of cellulose were characterized using X-ray diffraction (XRD). XRD results showed that the obtained product was in a form of cellulose Iᵦ structure, it is found that the treated cellulose by chemical treatment had a higher crystallinity than untreated cellulose. Thermal analysis was studied by Differential Scanning Calorimeter (DSC) which found that the microcrystalline cellulose had a higher thermal degradation than microfibrils cellulose.